Impact of chia seed protein hydrolysate and apple pomace pectin on the properties of egg-free mayonnaise - Sahar Abdoollahi; Peiman Ariaii; Seyed Ebrahim Hosseini; Mahro Esmaeili; Roya Bagheri (Heliyon)
This study investigates the properties of egg-free mayonnaise prepared using chia seed protein hydrolysate (CSPH) and pectin extracted from apple pomace (PA) as alternatives to egg, comparing it to traditional egg-based mayonnaise. Chia seed protein was hydrolyzed using Protamex and Bromelain enzymes, while apple pectin was extracted through acid hydrolysis at 90 °C. Four mayonnaise treatments were prepared: T1 (control: 6 % egg), T2 (4 % egg + 1 % CSPH + 1 % PA), T3 (2 % egg + 2 % CSPH + 2 % PA), and T4 (0 % egg + 3 % CSPH + 3 % PA). The physicochemical, textural, and sensory properties of the mayonnaise samples were evaluated. The CSPH produced with the Protamex enzyme exhibited a higher protein content and greater degree of hydrolysis (P < 0.05), establishing it as a suitable egg substitute. Replacing egg with CSPH and PA resulted in increased acidity, physical and thermal stability, viscosity, firmness, and adhesiveness of the mayonnaise, while reducing lightness, pH, and overall sensory scores. Treatments T3 and T4 demonstrated superior overall properties compared to other treatments; however, T3 received the highest sensory scores. These findings suggest that pectin and hydrolyzed protein can effectively replace egg in mayonnaise production, offering a viable alternative for individuals with egg allergies and those seeking healthier options.